Le Petit Nicolas and the Ontological in Schooling (LEARNing Landscapes, 2018)
“School as a site for the production of persons” (Packer & Greco-Brooks, 1999) is discussed in this article through an exploration of children’s growth as students. Drawing on Nicholas’ school stories from Rene Goscinny and Jean-Jacque Sempe’s well-known series entitled, Le Petit Nicolas, the kind of people we could become as students and teachers, even if fictional, is portrayed to highlight the importance of personhood and/or the ontological in schooling.
Keywords: ontology in schooling; stories of schooling; Le Petit Nicolas